Efektivitas Pembelajaran Kooperatif Tipe Talking Chip Untuk Meningkatkan Prestasi Siswa - Alwendi, Alwendi; Saputra Mandopa, Andi; Lubis, Fitri Romaito; Siregar, Martua (Jurnal Pendidikan Dewantara, 2024)
The research method used is classroom action research using two cycles carried out in the first semester with Number Pattern Material. The sample in this research was 30 students in class VIII-2 of SMP Negeri 7 Padangsidimpuan who would use the Talking Chip Learning Model in learning. The data collection techniques used were tests, questionnaires and observation sheets. The data analysis used is descriptive and inferential statistical analysis. The results of the research show that the ability of students' learning outcomes in learning Mathematics through the Talking Chip learning model for class VIII-2 students at SMP Negeri 7 Padangsidimpuan in the Number Patterns material for the 2021/2022 academic year has increased with a completion percentage of 93.3% in the "Good" category. Furthermore, the teacher's ability to manage learning increased to 97.90% with the "Very Good" category. For this reason, the expected results have been fulfilled because they are in accordance with the minimum good category with a percentage of 80%.